On the Development and Practice of AI Technology for Contemporary Popular Music Production. Issue 1 (7th February 2022) - Deruty, Emmanuel; Grachten, Maarten; Lattner, Stefan; Nistal, Javier; Aouameur, Cyran
Although the use of AI technology for music production is still in its infancy, it has the potential to make a lasting impact on the way we produce music. In this paper we focus on the design and use of AI music tools for the production of contemporary Popular Music, in particular genres involving studio technology as part of the creative process. First we discuss how music production practices associated with those genres can differ significantly from traditional views of how a musical work is created, and how this affects AI music technology. We argue that—given the role of symbolic representations in this context, as well as the integration of composition activities with editing and mixing—audio-based AI tools are better suited to support the artist's creative workflow than purely piano-roll/MIDI-based tools. Then we give a report of collaborations with professional artists, in which we look at how various AI tools are used in practice to produce music. We identify usage patterns as well as issues and challenges that arise in practical use of the tools. Based on this we formulate some recommendations and validation criteria for the development of AI technology for contemporary Popular Music.